2022
DOI: 10.1186/s12986-022-00673-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and metabolic syndrome in US children and adolescents: evidence from NHANES 2001–2018

Abstract: Background An increasing number of children and adolescents are affected by metabolic syndrome (MetS). Dietary inflammatory index (DII) was associated with MetS in adult population. This study aimed to determine the associations between DII scores, MetS, and MetS components among children and adolescents. Methods Data of children and adolescents in the National Health and Nutrition Examination Survey (NHANES) database 2001–2008 were obtained. DII w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This study documented a lower prevalence of MetS in adolescents (0.3–1.2%) compared to previous European (1.4–5.8%) [ 22 , 23 ] and American (National Health and Nutrition Examination Survey (NHANES), 6.8%) studies [ 24 ]. The population in this current study seems to be healthier, possibly due to the inclusion of adolescents from higher SES, a factor known to have an impact on adolescents’ cardiometabolic health [ 21 ].…”
Section: Discussionsupporting
confidence: 52%
“…This study documented a lower prevalence of MetS in adolescents (0.3–1.2%) compared to previous European (1.4–5.8%) [ 22 , 23 ] and American (National Health and Nutrition Examination Survey (NHANES), 6.8%) studies [ 24 ]. The population in this current study seems to be healthier, possibly due to the inclusion of adolescents from higher SES, a factor known to have an impact on adolescents’ cardiometabolic health [ 21 ].…”
Section: Discussionsupporting
confidence: 52%
“…For example, peripheral artery disease (PAD), which is strongly interlinked with inflammation, has been evaluated based on the dietary inflammatory index (DII) [ 176 ]. Consequently, a higher DII score has been associated with poor health and increased risks of obesity, cancer, cardiovascular disease (CVD), chronic obstructive pulmonary disease (COPD), depression, metabolic syndrome, T2D, and kidney stones [ 177 , 178 , 179 , 180 , 181 , 182 , 183 ]. This confirms the value of a diet rich in fibre, folate, and vitamins A, B6, C, and E in alleviating the prevalence of PAD [ 184 ].…”
Section: Obesity-related Complicationsmentioning
confidence: 99%
“…Meanwhile, it was reported that dietary pattern, evaluated by the dietary inflammatory index (DII), was associated with various inflammatory markers, including CRP, IL-6, and homocysteine [12,13]. In addition, higher DII scores have been shown to be associated with poor health and higher risk of diseases, such as obesity [14], various cancer [15,16], cardiovascular disease (CVD) [14,17], chronic obstructive pulmonary disease [18], depression [19,20], metabolic syndrome [21], type 2 diabetes [14,22], and kidney stones [23].…”
Section: Introductionmentioning
confidence: 99%